A Rare Case of Erdheim-Chester Disease (Non-Langerhans Cell Histiocytosis) with Concurrent Langerhans Cell Histiocytosis: A Diagnostic and Therapeutic Challenge - Hamza Hashmi; Drew Murray; John Greenwell; Marwan Shaikh; Soumit Basu; Maxwell Krem (Case Reports in Hematology)
Erdheim-Chester disease (ECD) is a rare non-Langerhans cell histiocyte disorder most commonly characterized by multifocal osteosclerotic lesions of the long bones demonstrating sheets of foamy histiocyte infiltrates on biopsy with or without histiocytic infiltration of extraskeletal tissues. ECD can be difficult to diagnose since it is a very rare disease that can affect many organ systems. Diagnosis is based on the pathologic evaluation of involved tissue interpreted within the clinical context. Patients who have the BRAF V600E mutation are treated first line with vemurafenib. For those without the mutation with symptomatic ECD, conventional or PEGylated interferon alpha is recommended. For patients who are either intolerant or nonresponsive to interferon alpha, systemic chemotherapy with or without corticosteroids can be used. We present a rare case of Erdheim-Chester disease with concurrent Langerhans cell histiocytosis which occurs in only one fifth of the cases and often presents as a diagnostic and therapeutic challenge.